ANALISIS PEMAHAMAN PEKERJA KONTRAK OUTSOURCING TERHADAP HAK-HAK PEKERJA YANG TERCANTUM DALAM UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN DI WILAYAH KOTA SURABAYA - Boong, Vicariya Retnowati; Ritonga, Rena Zefania (Jurnal Panorama Hukum, 2018)
The appearance of outsourcing companies shows that the high needs of companies and factories that exist for the use of labor in Indonesia. Security and cleaning service is a type of work that much needed in business world. The legal relationship between a company and an outsourced worker is fixed by a certain time work agreement (PKWT) which is regulated in Law No. 13/2003. The position of the outsourced contract workers is due to this kind of work is a complementary and the contract is only within a certain period. The outsourced contract workers have fundamental rights as stipulated in Law 13/2003, but this creates certain legal issues when in practice there are pros and cons due to differences of opinion between contract workers and companies and law understanding of outsourcing contract workers itself of their rights, whether rights at the end of their contratcs, rights obtained by workers if the agreement expires before the contract period is over, the right to rest and the right to obtain health insurance (BPJS). Key words : PKWT, outsourced workers, workers rights in Law 13/2003